Industry Wage Differentials Revisited: A Longitudinal Comparison of Germany and USA (1984-1996) - John P. Haisken-DeNew; Christoph M. Schmidt (Institute for the Study of Labor (IZA), 1999)
In this paper, the inter-industry wage structure in West Germany and USA is compared using the German Socio-Economic Panel (GSOEP), the German Mikrozensus (MZ), the American Panel Study of Income Dynamics (PSID) and the American Current Population Survey (CPS) from 1984 to 1996. Using a sample of prime age full-time employed males from the respective datasets, it is shown that the structure of wages has remained remarkably stable over this time period, and that the German structure resembles the American structure strongly. Cross-sectional and panel results are provided for both countries. Controlling for unobserved heterogeneity in the random effects panel estimations reduces the industry wage dispersion by about half. Thus, although the MZ and the CPS provide very large sample sizes, panel data sets (although typically smaller in sample size) are still very important in getting at the essence of the industry wage structure and the absolute level of industry wage dispersion. In calculating inter-industry wage differentials as deviations from a hypothetical employment-share weighted mean, we use the methodology as described in Haisken-DeNew and Schmidt (1997) of calculating exact differentials and their respective standard errors.
Keywords: C20; J31; 330; Inter-Industry Wage Differentials; West Germany; USA; dummy variables; restricted least squares; weighted standard deviation; Sektorale Lohnstruktur; Mikroökonometrie; Vergleich; Schätzung; Deutschland; USA